2014
DOI: 10.1097/qad.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Plasma plasminogen activator inhibitor-1 predicts myocardial infarction in HIV-1-infected individuals

Abstract: High levels of PAI-1 were associated with risk of first-time MI in HIV-1-infected individuals independently of cardiovascular risk factors, HIV parameters and antiretroviral therapy. Therefore PAI-1 may be used for risk stratification and prediction of CHD, but further studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
5
25
0
2
Order By: Relevance
“…This association has also been confirmed in a recent meta-analysis (25). Overall, the relevance of our results can be better understood when we consider that the risk of MI increases of about 1% each 1 ng/ml increase in PAI-1 levels (26). In our study population we have found a Ϸ11 ng/ml difference in PAI-1 levels among SH patients and controls, which, according to above reported data, should confer a Ϸ11% increase in the thrombotic risk in this clinical setting.…”
Section: Discussionsupporting
confidence: 46%
“…This association has also been confirmed in a recent meta-analysis (25). Overall, the relevance of our results can be better understood when we consider that the risk of MI increases of about 1% each 1 ng/ml increase in PAI-1 levels (26). In our study population we have found a Ϸ11 ng/ml difference in PAI-1 levels among SH patients and controls, which, according to above reported data, should confer a Ϸ11% increase in the thrombotic risk in this clinical setting.…”
Section: Discussionsupporting
confidence: 46%
“…The overall heterogeneity across studies is high (I 2 =71.5%, P <0.001; Figure 2A). The association estimate is reduced but remains significant in studies using a multivariable‐adjusted model (OR=1.46; 95% CI: 1.13, 1.88; Figure 2B),11, 12, 13, 14, 16, 17, 18, 19, 20, 21, 22, 23, 31 with a lower overall heterogeneity compared with studies applying only an age‐and sex‐adjusted model (I 2 =55.7%, P =0.008; Figure 2B). In the subgroup meta‐analysis based on different PAI‐1 quantile scales, heterogeneity is observed most strongly in the quartile subgroup in both age‐ and sex‐adjusted model (I 2 =81.6%, P <0.001; Figure 2A) and the multivariable‐adjusted model (I 2 =61.7%, P <0.016; Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies that adjusted only for age and sex reported association between PAI‐1 and CHD incidence (Table S1), while 13 studies found the same association following adjustment for multiple covariates (eg, BMI, blood glucose, blood lipids, and blood pressure; Table S1). 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 31 Covariates used in each study that included multivariable‐adjusted models are shown in Table S1. Detailed literature screening procedure is presented in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations